Responsabilidad ambiental de la juventud costarricense: una posibilidad para garantizar el futuro - Vega García, Heidy (2013)
The current generation of young joins previous generations (grandparents and parents) and the generations that are to come (children and grandchildren). This generation has a dual responsibility, to his family and country (citizenship) and to the world (humanity). Recent indicators show that Costa Rica faces serious environmental challenges. Against this background, it is mentioned aspects of how the National University can contribute to environmental leadership in young Costa Ricans, so that they have the opportunity to secure the country’s future.